Examination and Treatment Scenario in Urogynecology Case During COVID-19 Pandemic: A Review - Eighty Mardiyan Kurniawati; Gatut Hardiyanto; Hari Paraton; Nur Anisah Rahmawati (Institute of Medico-legal Publications Pvt Ltd, 2021)
The number of COVID-19 cases continues to increase therefore health services in hospitals must adapt to the COVID-19 pandemic. One of the services that must be affected is urogynecology services. This study aims to examine scenarios in the examination and treatment of patients with urogynecological cases in hospitals during a pandemic. A non-systematic review examines several scientific articles related to recommendations. The articles were searched through the PubMed and Google Scholar databases with the keywords “urogynecology patient” or “hospital” or “treatment” or “urogynecology care” and “COVID-19”. Data is arranged in the form of scenarios and narrative reviews. The scenario carried out is telemedicine, except for certain severe cases, so one must go to the hospital with a record of patient protection against COVID-19. It is possible to use online to prevent the accumulation of patients in the hospital. Management emphasizes non-surgical solutions such as lifestyle, nutritional patterns, behavioral concepts, and periodic drug administration. Implementation is carried out with preconditions, namely patient safety, an integrated system related to payment and prescription of drugs. Things that need to be underlined in telemedicine governance are the need for adequate counseling and good cooperation between doctors and patients because this will affect diagnosis and management. This effort makes it possible to break the chain of infection in urogynecology services and the need for further research related to a complete and comprehensive application system